GENETIC CONSERVATION IN VULTUR GRYPHUS (LINNEAUS, 1758) (FALCONIFORMES: CATHARTIDAE) - Olano, Paola (2021)
Vultur gryphus (Linneaus, 1758) is distributed throughout the entire length of the Andes mountain ranges, however, habitat destruction, overpopulation, agriculture and among other factors have fragmented its habitat, causing this to affect its population and placing it in the low red book the Endangered category (EN); the fragmentation of its habitat does not allow the condor to find nesting places and can increase its population, this brings the reduction of genetic variability, genetic diversity, mutation, among others. The objective is to recognize the effects of fragmentation in relation to the population genetic variability and conservation of the Andean condor in Peru. An extensive search for information was carried out in Google search engine, ResearchGate, Scielo and Redalyc, of publications in English or Spanish between 1980 - 2020, in which different search terms were used such as: "Conservation condors", "Conservation strategies","Vultur gryphus", "Habitat fragmentation", "Conservation of the Condor", etc. A total of 70 references were registered between the years 1931-2020, of which only 57 were initially accepted, and 13 were eliminated due to being duplicates. Of the 57 remaining references, the title, abstract and full text were analyzed, which led us to prioritize only 21 references to carry out this work, while the remaining 36 were eliminated because they did not meet the inclusion criteria. Currently, the fragmentation in the conservation of habitat in V. gryphus at the South American level is the main cause for the reduction of genetic variability, genetic structure, and loss of genetic diversity.